Nano Strategies for Artemisinin Derivatives to Enhance Reverse Efficiency of Multidrug Resistance in Breast Cancer - Zhang, Xueyan; Li, Na; Zhang, Guoqin; Li, Jiayang; Liu, Yi; Wang, Meng; Ren, Xiaoliang (Current Pharmaceutical Design, 2023)
Artemisinin (ART) has been found to exert anti-tumor activity by regulating the cell cycle, inducing apoptosis, inhibiting angiogenesis and tumor invasion and metastasis. Its derivatives (ARTs) can regulate the expression of drug-resistant proteins and reverse the multidrug resistance (MDR) of tumor cells by inhibiting intracellular drug efflux, inducing apoptosis and autophagy of tumor cells, thus enhancing the sensitivity of tumor cells to chemotherapy and radiotherapy. Recent studies have shown that nanodrugs play an important role in the diagnosis and treatment of cancer, which can effectively solve the shortcomings of poor hydrophilicity and low bioavailability of ARTs in the human body, prolong the in vivo circulation time, improve the targeting of drugs (including tumor tissues or specific organelles), and control the release of drugs in target tissues, thereby reducing the side effect. This review systematically summarized the latest research progress of nano-strategies of ARTs to enhance the efficiency of MDR reversal in breast cancer (BC) from the following two aspects: (1) Chemicals encapsulated in nanomaterials based on innovative anti-proliferation mechanism: non-ABC transporter receptor candidate related to ferroptosis (dihydroartemisinin/DHA analogs). (2) Combination therapy strategy of nanomedicine (drug-drug combination therapy, drug-gene combination, and chemical-physical therapy). Self-assembled nano-delivery systems enhance therapeutic efficacy through increased drug loading, rapid reactive release, optimized delivery sequence, and realization of cascade-increasing effects. New nanotechnology methods must be designed for specific delivery routines to achieve targeting administration and overcome MDR without affecting normal cells. The significance of this review is to expect that ART and ARTs can be widely used in clinical practice. In the future, nanotechnology can help people to treat multidrug resistance of breast cancer more accurately and efficiently.
Keywords: Artemisinin